2019
DOI: 10.1167/19.6.19
|View full text |Cite
|
Sign up to set email alerts
|

Distinct temporal mechanisms modulate numerosity perception

Abstract: Our ability to process numerical and temporal information is an evolutionary skill thought to originate from a common magnitude system. In line with a common magnitude system, we have previously shown that adaptation to duration alters numerosity perception. Here, we investigate two hypotheses on how duration influences numerosity perception. A channelbased hypothesis predicts that numerosity perception is influenced by adaptation of onset/offset duration channels which also encode numerosity or wire together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…If, on the other hand, serial dependence involves dimension-specific mechanisms, or it is specific for the task at hand, then we should expect only an effect of inducer duration on reference duration and of inducer numerosity on reference numerosity. Note that we predict a direct effect of the magnitude dimensions of the inducer on the magnitude perception of the reference – similar for instance to what has been observed in the case of adaptation ( Tsouli, Dumoulin, te Pas, & van der Smagt, 2019 ; Tsouli, van der Smagt, Dumoulin, & te Pas, 2019 )—and not an effect on the perception of the reference that is mediated by a biased perception of the inducer itself.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…If, on the other hand, serial dependence involves dimension-specific mechanisms, or it is specific for the task at hand, then we should expect only an effect of inducer duration on reference duration and of inducer numerosity on reference numerosity. Note that we predict a direct effect of the magnitude dimensions of the inducer on the magnitude perception of the reference – similar for instance to what has been observed in the case of adaptation ( Tsouli, Dumoulin, te Pas, & van der Smagt, 2019 ; Tsouli, van der Smagt, Dumoulin, & te Pas, 2019 )—and not an effect on the perception of the reference that is mediated by a biased perception of the inducer itself.…”
Section: Introductionsupporting
confidence: 84%
“…Previous results also support this idea. Indeed, it has been shown than duration adaptation biases the perceived numerosity of a subsequent stimulus in a repulsive fashion ( Tsouli, Dumoulin, et al, 2019 ; Tsouli, van der Smagt, et al, 2019 ). Additionally, repulsive adaptation effects across numerosity and duration also appear to be asymmetric, with an opposite pattern compared to magnitude integration, that is, duration adaptation affects perceived numerosity, but numerosity adaptation does not affect perceived time ( Tsouli, Dumoulin, et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories are supported by neuroimaging findings showing overlapping brain activations during different quantity tasks [5,7,141] and perceptual interactions between quantity dimensions. However, overlapping brain activations do not necessarily imply a common neural code for different quantities, and recent behavioral studies examining the interaction of different quantities paint a more complex picture [78,142,143]. Furthermore, evidence from animal electrophysiology and human fMRI are not entirely consistent with the idea of a common neural mechanism Selective responses to each quantity are organized into topographic maps, that is, regions where the preferred quantity changes gradually across the cortical surface.…”
Section: Neural Tuning Underlies Interactions Between Different Quant...mentioning
confidence: 98%
“…In contrast, there is insufficient evidence to support/reject the effect of numerosity adaptation on duration judgment. Successively, Tsouli et al (2019b), investigated how duration influences numerosity perception, and they showed that at least two temporal mechanisms are involved. Tsouli et al (2019b) found that: (i) the effect of "adaptation to duration" on numerosity perception is independent from adaptation duration (channel based hypothesis); (ii) the effect of "adaptation to numerosity" on numerosity perception is driven by the total duration of the adaptation trials (strength-of-adaptation hypothesis).…”
Section: Introductionmentioning
confidence: 99%